EFFECTS OF INTERVENTIONS ON THE EUTROPHICATION PROCESS OF PARANOA LAKE RESERVOIR OF BRASILIA, BRAZIL - Angelini, Ronaldo (Associação Brasileira de Ciência Ecológica e Conservação (ABECO), 2009)
Long-term environmental monitoring of aquatic ecosystems is essential to understand their dynamics and to the proposition of management practices. Paranoa Reservoir was created in 1959 and was subject to a long period of eutrophication. In this paper, data obtained by the monitoring program carried out by the “Companhia de Abastecimento e Saneamento de Brasilia”, between 1976 and 2001, were evaluated to measure the effects of three direct interventions on water quality (as measured by water transparency, P-total and chlorophyll-a concentrations): the activation of two water treatment plants (01/1993); the proper operation of these plants (01/1996), and a major flushing event (sudden release of water in 11/1999). The following results were obtained: i) the first intervention had no effect on the mean values of the variables analyzed; ii) the chlorophyll-a and total phosphorus concentrations significantly declined after the second intervention; iii) water transparency increased after the third intervention. An apparent mechanism of phosphorus feedback supported by phytoplankton was interrupted by the flushing and, after that intervention, the primary production of Paranoa Reservoir declined to a new level. The dataset obtained by the monitoring program was essential to understand this process and, therefore, the continuity (and even amplification) of this program was fully justified.